2016
DOI: 10.1002/ppul.23500
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vitamin D against hyperoxia-induced lung injury in newborn rats

Abstract: Vitamin D seems to protect hyperoxia-induced lung injury in newborn rats. Pediatr Pulmonol. 2017;52:69-76. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
0
21
0
3
Order By: Relevance
“…Our previous study found that vitamin D receptor-knockout mice showed a more intense inflammatory response to LPS and vitamin D treatment decreased the secretion of pro-inflammatory cytokines in LPS-induced lung injury (11). The anti-apoptotic role of vitamin D was also demonstrated in pulmonary tissue (10). Agonists of vitamin D receptor relieved cardiomyocyte apoptosis in a model of myocardial ischemic-reperfusion (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that vitamin D receptor-knockout mice showed a more intense inflammatory response to LPS and vitamin D treatment decreased the secretion of pro-inflammatory cytokines in LPS-induced lung injury (11). The anti-apoptotic role of vitamin D was also demonstrated in pulmonary tissue (10). Agonists of vitamin D receptor relieved cardiomyocyte apoptosis in a model of myocardial ischemic-reperfusion (27).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we took the experimental hyperoxia model as reference and formed the chain of inflammatory events. 12 These were divided into four groups: normoxia control group (group-1), normoxia+lycopene group (group-2), hyperoxia control group (group--3) and hyperoxia+lycopene group (group-4); there were 10 newborn rats in each group. The dosage study by Bignotto et al 13 has been taken as a basis for the anti-inflammatory effect of lycopene.…”
Section: Methodsmentioning
confidence: 99%
“…; and, finally, the group-4 was given a single dose of lycopene along with oxygen above 85 %. 12 The study was completed on the postnatal 11th day and the animals were sacrificed. The brain tissues were quickly removed and used for histological analysis and ELISA studies ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in Pediatric Pulmonology published in 2017 used relatively high oxygen concentrations over a prolonged period, well past the initiation of the saccular stage of lung development, and inevitably productive of ROS levels unlikely to be experienced in neonatal intensive care. Kose et al to their credit tested varied doses of vitamin D on hyperoxia‐impaired lung development in newborn Wistar rats, and found that there were dose‐dependent, reciprocal effects on TUNEL‐labeled cells and proliferating cell nuclear antigen positive cells. This is a useful advance as effects of vitamin D on cell proliferation and differentiation are known to be concentration dependent .…”
Section: Experimental and Clinical Bpd And Sequelaementioning
confidence: 99%